2017
DOI: 10.1186/s12864-017-4095-6
|View full text |Cite
|
Sign up to set email alerts
|

Dual RNA-seq reveals no plastic transcriptional response of the coccidian parasite Eimeria falciformis to host immune defenses

Abstract: BackgroundParasites can either respond to differences in immune defenses that exist between individual hosts plastically or, alternatively, follow a genetically canalized (“hard wired”) program of infection. Assuming that large-scale functional plasticity would be discernible in the parasite transcriptome we have performed a dual RNA-seq study of the lifecycle of Eimeria falciformis using infected mice with different immune status as models for coccidian infections.ResultsWe compared parasite and host transcri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

4
2

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 78 publications
5
25
0
Order By: Relevance
“…falciformis BayerHaberkorn1970 (Haberkorn, 1970) Between the two E. falciformis isolates BayerHaberkorn1970 and Brandenburg88 we observed only slight differences in the length of the pre-patent period (time until oocyst shedding, starting at 6 vs. 7 dpi). These results are in agreement with previous reports from the same host (NMRI mice) and the BayerHaberkorn1970 isolate (Stange et al, 2012;Schmid et al, 2012Schmid et al, , 2014Ehret et al, 2017). The pre-patent period for the wild derived E. falciformis isolate (7 dpi) corresponds to that reported for the parasite isolate E. falciformis var praghensis (Mesfin et al, 1978;Kasai et al, 1991), but Mahrt and Shi (1988) and Schito et al (1996) demonstrated slightly longer pre-patent periods (7 or 8 dpi) also in other E. falciformis infections.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…falciformis BayerHaberkorn1970 (Haberkorn, 1970) Between the two E. falciformis isolates BayerHaberkorn1970 and Brandenburg88 we observed only slight differences in the length of the pre-patent period (time until oocyst shedding, starting at 6 vs. 7 dpi). These results are in agreement with previous reports from the same host (NMRI mice) and the BayerHaberkorn1970 isolate (Stange et al, 2012;Schmid et al, 2012Schmid et al, , 2014Ehret et al, 2017). The pre-patent period for the wild derived E. falciformis isolate (7 dpi) corresponds to that reported for the parasite isolate E. falciformis var praghensis (Mesfin et al, 1978;Kasai et al, 1991), but Mahrt and Shi (1988) and Schito et al (1996) demonstrated slightly longer pre-patent periods (7 or 8 dpi) also in other E. falciformis infections.…”
Section: Discussionsupporting
confidence: 94%
“…The output of oocysts in our study (for all isolates) was similar or only slightly lower than in previous reports (Schmid et al, 2014;Ehret et al, 2017). Our observation regarding the lifecycle progression of E. ferrisi, agree with the initial description of the life cycle in Mus musculus (Ankrom et al, 1975).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Studies of the European eel using RNA-seq to examine gene expression have found that genes involved in an immune response were differentially expressed in the swim bladder (the site of infection) of naturally infected eels (i.e., containing parasites of all stages) (Schneebauer, Dirks, & Pelster, 2017), as well as in the spleen and the head kidney (immune organs) very soon after experimental infection F I G U R E 1 The Japanese eel (Anguilla japonica) is the native host of Anguillicola crassus, a parasitic swim bladder nematode invasive in the European eel (Anguilla anguilla) (3 dpi, i.e., containing only larvae) . Differential regulation of processes associated with both the innate and the adaptive immune system in immune organs and at the site of infection is a common feature in natural and experimental infections in vertebrates (e.g., Alvarez Rojas et al, 2015;Babayan et al, 2018;Huang et al, 2016) and the gradual shift from the regulation of innate to adaptive immune processes can be observed in gene expression studies (Ehret, Spork, Dieterich, Lucius, & Heitlinger, 2017). Additionally, parasite infections cause differential expression of genes not directly related to an immune response, such as those involved in metabolic processes, tissue repair, or organ function and development (Alvarez Rojas et al, 2015;Babayan et al, 2018;Ronza et al, 2016;Zhang et al, 2017) and this has also been observed in the European eel Schneebauer et al, 2017).…”
mentioning
confidence: 99%